Eating behaviors and dietary pattern in children with Autism Spectrum Disorder (ASD) in Puncak Alam, Selangor, Malaysia/ Atasya Syuhada Mohamad and Farhanah Ahmad Shuhaimi - Mohamad, Atasya Syuhada; Ahmad Shuhaimi, Farhanah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
An Autism Spectrum Disorder (ASD) is a neurological and progressive disorder that starts early in childhood and persists throughout a person's life. It is assessed and diagnosed by medical professionals and the symptoms associated with ASD can be detected in childhood as early as 2 years of a child's age. Children with ASD were known to have certain eating habits that affecting their dietary intake. Thus, this study aims to determine the eating behaviors and dietary pattern in children with ASD in Puncak Alam, Selangor. This cross-sectional study used a non-probability sampling with validated eating behavior questionnaire and food frequency questionnaire (FFQ) as the research instrument. From this study, it was found that, children with ASD positively relate with several eating behaviors. The most associated eating behaviors are refusing food of certain textures and refusing food from certain food group (100%). This followed with behavior of sometimes they eat only a small amount but in repeated times (73.9%), some of them often eat too much (56.5%) and some of them frequently refuses food of certain colors (47.8%). The children with ASD mostly associated with the Western pattern, followed by the Malay pattern, while the healthy pattern mostly not preferred by the children.